Seksagesimal Sistem Bilangan Perenampuluhan atau Basis 60 - Hafizhah Khairana; Ariantje Dimpudus (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
This study aims to gather sufficient information about the sexagesimal base 60 number system. This research method is a literature study that collects some previous studies to answer about the sexagesimal base 60 number system. The results of this research show that the sexagesimal or sixtieth number system is the same calculation as Babylonian people's astronomical calculations, in their use sexagesimals can be said to be easier to use than decimal numbers, and to this day the sexagesimal number system is still used in a modified form to measure time, angles, geographic coordinates, and is still used in the field of astronomy.